2020
DOI: 10.1049/iet-esi.2019.0123
|View full text |Cite
|
Sign up to set email alerts
|

Optimal coordinative operation strategy of the electric–thermal–gas integrated energy system considering CSP plant

Abstract: Concentrating solar power (CSP) plant, which has great controllability and scheduling flexibility, is a promising renewable energy power generation technology. The reasonable scheduling of a CSP plant can effectively reduce the operating cost of the integrated energy system (IES). In this context, a day‐ahead optimal coordinative operation model of the electric–thermal–gas IES considering CSP plant is proposed in this study with the objective function of minimising the operating cost of the IES. In the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Analogously, a digester can be added to the EH to interconnect the EH with a biogas-electric multi-energy system to form a biogas-solar-wind complementary model, which improves the absorption rate of renewable energy and reduces the operation cost of the IES [6]. A concentrating solar power plant model that couples the power grid and the heating network, making the internal components of the EH more diversified, was established in [7]. The results showed that the EH can lower the operation cost and promote the wind power penetration of the IES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously, a digester can be added to the EH to interconnect the EH with a biogas-electric multi-energy system to form a biogas-solar-wind complementary model, which improves the absorption rate of renewable energy and reduces the operation cost of the IES [6]. A concentrating solar power plant model that couples the power grid and the heating network, making the internal components of the EH more diversified, was established in [7]. The results showed that the EH can lower the operation cost and promote the wind power penetration of the IES.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, exploring the optimal algorithms suitable for the OEF problem is also important research in the field of IESs. Numerical algorithms, such as mixed-integer linear programming [7,12,13], Benders decomposition [14], and second-order cone programming [15], are fast in convergence. However, the implementation of the numerical algorithm is complicated, and they may not converge when the objective function is discontinuous or contains multiple extreme points.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid escalation of energy consumption, the efficient utilisation of energy in the integrated energy system (IES) has become a hot topic for solving the problem of the energy crisis. IES involves the production, transmission, and utilisation of multiple energy including electricity, heating, cooling, and gas [1,2], which can improve the overall energy utilisation efficiency by using and incorporating multiple energy sources to supply multiple energy demands [3,4]. Demand response (DR) is a significant way for the demand side to participate in grid interaction, which has been widely used for optimal planning [5][6][7][8] and optimal scheduling [9][10][11][12] in power systems to maintain frequency stability and power balance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…An IDR strategy combining energy substitution and load shifting is developed in [17] to exploit the demand flexibility of multi-energy buildings. For the storage side, the optimal scheduling strategies of actual multiple energy storage devices (AMESDs) in ILES, that is, electricity storage device, heat storage device and gas storage device, are studied in [18][19][20], respectively.…”
Section: Introductionmentioning
confidence: 99%